Explore a vast range of topics and get informed answers at IDNLearn.com. Our experts provide timely, comprehensive responses to ensure you have the information you need.
Sagot :
Let's solve the expression step-by-step.
Given the expression:
[tex]\[ \frac{a + \sqrt{a^2 - b^2}}{a - \sqrt{a^2 - b^2}} + \frac{a - \sqrt{a^2 - b^2}}{a + \sqrt{a^2 - b^2}} \][/tex]
For simplicity, assign:
[tex]\[ x = a + \sqrt{a^2 - b^2} \][/tex]
[tex]\[ y = a - \sqrt{a^2 - b^2} \][/tex]
Rewrite the expression in terms of \(x\) and \(y\):
[tex]\[ \frac{x}{y} + \frac{y}{x} \][/tex]
We know that the sum of two fractions can be expressed as:
[tex]\[ \frac{x}{y} + \frac{y}{x} = \frac{x^2 + y^2}{xy} \][/tex]
Next, find \(x^2\) and \(y^2\).
[tex]\[ x = a + \sqrt{a^2 - b^2} \implies x^2 = \left(a + \sqrt{a^2 - b^2}\right)^2 = a^2 + 2a\sqrt{a^2 - b^2} + (a^2 - b^2) = 2a^2 - b^2 + 2a\sqrt{a^2 - b^2} \][/tex]
[tex]\[ y = a - \sqrt{a^2 - b^2} \implies y^2 = \left(a - \sqrt{a^2 - b^2}\right)^2 = a^2 - 2a\sqrt{a^2 - b^2} + (a^2 - b^2) = 2a^2 - b^2 - 2a\sqrt{a^2 - b^2} \][/tex]
Sum of \(x^2\) and \(y^2\):
[tex]\[ x^2 + y^2 = \left(2a^2 - b^2 + 2a\sqrt{a^2 - b^2}\right) + \left(2a^2 - b^2 - 2a\sqrt{a^2 - b^2}\right) = 4a^2 - 2b^2 \][/tex]
Next, find \(xy\):
[tex]\[ x \cdot y = \left(a + \sqrt{a^2 - b^2}\right)\left(a - \sqrt{a^2 - b^2}\right) = a^2 - \left(\sqrt{a^2 - b^2}\right)^2 = a^2 - (a^2 - b^2) = b^2 \][/tex]
Now, use the values of \(x^2 + y^2\) and \(xy\):
[tex]\[ \frac{x}{y} + \frac{y}{x} = \frac{x^2 + y^2}{xy} = \frac{4a^2 - 2b^2}{b^2} = \frac{4a^2}{b^2} - \frac{2b^2}{b^2} = \frac{4a^2}{b^2} - 2 \][/tex]
Thus, the value of the given expression is:
[tex]\[ \boxed{\frac{4a^2}{b^2} - 2} \][/tex]
Given the expression:
[tex]\[ \frac{a + \sqrt{a^2 - b^2}}{a - \sqrt{a^2 - b^2}} + \frac{a - \sqrt{a^2 - b^2}}{a + \sqrt{a^2 - b^2}} \][/tex]
For simplicity, assign:
[tex]\[ x = a + \sqrt{a^2 - b^2} \][/tex]
[tex]\[ y = a - \sqrt{a^2 - b^2} \][/tex]
Rewrite the expression in terms of \(x\) and \(y\):
[tex]\[ \frac{x}{y} + \frac{y}{x} \][/tex]
We know that the sum of two fractions can be expressed as:
[tex]\[ \frac{x}{y} + \frac{y}{x} = \frac{x^2 + y^2}{xy} \][/tex]
Next, find \(x^2\) and \(y^2\).
[tex]\[ x = a + \sqrt{a^2 - b^2} \implies x^2 = \left(a + \sqrt{a^2 - b^2}\right)^2 = a^2 + 2a\sqrt{a^2 - b^2} + (a^2 - b^2) = 2a^2 - b^2 + 2a\sqrt{a^2 - b^2} \][/tex]
[tex]\[ y = a - \sqrt{a^2 - b^2} \implies y^2 = \left(a - \sqrt{a^2 - b^2}\right)^2 = a^2 - 2a\sqrt{a^2 - b^2} + (a^2 - b^2) = 2a^2 - b^2 - 2a\sqrt{a^2 - b^2} \][/tex]
Sum of \(x^2\) and \(y^2\):
[tex]\[ x^2 + y^2 = \left(2a^2 - b^2 + 2a\sqrt{a^2 - b^2}\right) + \left(2a^2 - b^2 - 2a\sqrt{a^2 - b^2}\right) = 4a^2 - 2b^2 \][/tex]
Next, find \(xy\):
[tex]\[ x \cdot y = \left(a + \sqrt{a^2 - b^2}\right)\left(a - \sqrt{a^2 - b^2}\right) = a^2 - \left(\sqrt{a^2 - b^2}\right)^2 = a^2 - (a^2 - b^2) = b^2 \][/tex]
Now, use the values of \(x^2 + y^2\) and \(xy\):
[tex]\[ \frac{x}{y} + \frac{y}{x} = \frac{x^2 + y^2}{xy} = \frac{4a^2 - 2b^2}{b^2} = \frac{4a^2}{b^2} - \frac{2b^2}{b^2} = \frac{4a^2}{b^2} - 2 \][/tex]
Thus, the value of the given expression is:
[tex]\[ \boxed{\frac{4a^2}{b^2} - 2} \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Thanks for visiting IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more helpful information.